Induction of procalcitonin in liver transplant patients treated with anti-thymocyte globulin - Zazula, Roman; Prucha, Miroslav; Tyll, Tomas; Kieslichova, Eva (Critical care (London, England), 2007)
INTRODUCTION: The aim of this study was to compare the early postoperative kinetics of procalcitonin (PCT) and C-reactive protein (CRP) serum levels in patients undergoing orthotopic liver transplantation (OLTx) with different immunosuppressive regimens. METHODS: PCT and CRP serum concentrations were measured in a group of 28 OLTx recipients before induction of anesthesia, at 4 and 8 hours following graft reperfusion, and daily until postoperative day 4. The same parameters were determined in 12 patients undergoing liver resection without conjunctive immunosuppressive therapy. Summary data are expressed as medians and ranges. Two-tailed nonparametric tests were performed and considered significant at p values of less than 0.05. RESULTS: The highest serum levels of PCT (median 3.0 ng/mL, minimum 1.4 ng/mL, maximum 13.9 ng/mL) were found in patients after OLTx without ATG therapy, on postoperative day 1. In patients with ATG administration, PCT levels were highly increased on postoperative day 1 (median 53.0 ng/mL, minimum 7.9 ng/mL, maximum 249.1 ng/mL). Thereafter, PCT values continuously decreased independently of further ATG administration in both groups of patients. No evidence of infection was present in either group. In 12 patients undergoing liver resection, peak serum PCT levels did not exceed 3.6 ng/mL. CRP serum levels in a group of patients with and without ATG therapy increased significantly on postoperative day 1, followed by a decrease. The highest levels of CRP were found in patients after liver resection on postoperative day 2 and decreased thereafter. CONCLUSION: ATG administration to patients with OLTx is associated with an increase in serum PCT levels, with peak values on postoperative day 1, and this was in the absence of any evidence of infection. The results of this study indicate that ATG immunosuppressive therapy is a stimulus for the synthesis of PCT.
Keywords: Protein Precursors; proteinové prekurzory; Postoperative Complications; antilymfocytární sérum; Calcitonin Gene-Related Peptide; C-reaktivní protein; Humans; imunosupresiva; peptid spojený s genem pro kalcitonin; Calcitonin; C-Reactive Protein; lidé; pooperační komplikace; Immunosuppressive Agents; kalcitonin; Antilymphocyte Serum; Liver Transplantation; transplantace jater